Sputtered Titanium Nitride: A Bifunctional Material for Li-Ion Microbatteries. Issue 4 (13th January 2015) - Freixas, Jeremy; Eustache, Etienne; Roussel, Pascal; Brillard, Charlene; Deresmes, Dominique; Nuns, Nicolas; Rolland, Nathalie; Brousse, Thierry; Lethien, Christophe
Abstract : Sputtered TiN bifunctional thin films have been deposited in order to act simultaneously as a current collector for the negative electrode and as a lithium ion diffusion barrier in a Li-ion microbattery fabricated on a silicon wafer. Sputtered parameters have been optimized to reach a dense and columnar morphology with no void and low surface roughness. For the films deposited at 450°C, the TiN resistivity is close to 105 μohm·cm. The normalized surface capacity of the optimized thin film (0.16 μAh/cm 2 ·μm −1 ) is one order of magnitude lower than the lowest reported capacities for TiN thin films (either by sputtering technique or by atomic layer deposition). The role of TiN thin film as lithium ion diffusion barrier has been evidenced by performing galvanostatic charge/discharge and concomitant depth profile analyses of a sputtered gold negative electrode deposited on a silicon wafer with and without the use of a TiN interlayer.